Studium antropologiczno-socjologiczne emigrantów żydowskich do Palestyny - Sikora, Paweł (Polskie Towarzystwo Antropologiczne, 1987)
The materials were collected in 1936. The anthropological feature of the investigated group are presented against the background of data on Jews studying at the University in Lvov in 1927.
Antropo-sociological study on Jewish emigrants to Palestine